Micro‐trichome as a class I homeodomain‐leucine zipper gene regulates multicellular trichome development in Cucumis sativus. Issue 11 (24th April 2015) - Zhao, Jun‐Long; Pan, Jun‐Song; Guan, Yuan; Zhang, Wei‐Wei; Bie, Bei‐Bei; Wang, Yun‐Li; He, Huan‐Le; Lian, Hong‐Li; Cai, Run
Abstract: Plant trichomes serve as a highly suitable model for investigating cell differentiation at the single‐cell level. The regulatory genes involved in unicellular trichome development in Arabidopsis thaliana have been intensively studied, but genes regulating multicellular trichome development in plants remain unclear. Here, we characterized Cucumis sativus (cucumber) trichomes as representative multicellular and unbranched structures, and identified Micro‐trichome ( Mict ), using map‐based cloning in an F2 segregating population of 7, 936 individuals generated from a spontaneous mict mutant. In mict plants, trichomes in both leaves and fruits, are small, poorly developed, and denser than in the wild type. Sequence analysis revealed that a 2, 649‐bp genomic deletion, spanning the first and second exons, occurred in a plant‐specific class I homeodomain‐leucine zipper gene. Tissue‐specific expression analysis indicated that Mict is strongly expressed in the trichome cells. Transcriptome profiling identified potential targets of Mict including putative homologs of genes known in other systems to regulate trichome development, meristem determinacy, and hormone responsiveness. Phylogenic analysis charted the relationships among putative homologs in angiosperms. Our paper represents initial steps toward understanding the development of multicellular trichomes. Abstract : Trichomes of cucumber are representative multicellular and unbranched structures. We identified Micro‐trichome (Mict) as a novel class I homeodomain‐leucine zipper gene using map‐based cloning. Mict represses trichome spacing and is strongly expressed in trichomes. In addition, transcriptome profiling and phylogenic analysis were utilized to identify potential targets and to chart the relationships among putative homologsin angiosperms respectively.